Do Attitudes Towards E-Taxation Impact Tax Compliance? - Fachrezzi, Bima Rafly; Tjaraka, Heru (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2024)
This research aims to collect empirical data on the influence of e-tax perceptions and tax sanctions on compliance, using risk perception as a moderating factor. The data analysis was conducted using WarpPLS. The study sample comprised 34 taxpayers from the hotel, restaurant, and entertainment sectors. The findings indicate that risk preference did not affect the correlation between e-tax and tax sanctions on compliance in Banyuwangi. This highlights that the implementation of electronic taxation does not automatically enhance tax compliance. This is attributed to taxpayers’ risk-neutral attitudes, who believe that risk does not materially impact their business operations. Consequently, e-tax and its associated sanctions are not viewed as viable to foster compliance. This study uniquely focuses on taxpayers’ risk preferences as an internal factor, given their variability among taxpayers, particularly concerning e-tax adoption